Estudio de impacto ambiental de la granja avícola “El Camperito” ubicada en el sector Nueva Guinea del cantón Balsas, provincia de El Oro-Ecuador. - Romero Ramírez, Tatiana Anabell (2019)
An environmental impact study is a document that describes in detail the characteristics of a project or activity that is intended to be carried out or modified. It must provide information for the identification and interpretation of environmental impacts and describe the actions that will be taken to modify, correct and compensate for their negative effects. Thus, an environmental impact study was carried out on the "El Camperito" poultry farm located in the Nueva Guinea sector of the Balsas canton in the province of El Oro, considering three specific objectives for its development. In the first instance, the baseline survey was carried out in order to know the current state of the site where the farm is located, both in the abiotic, biotic and socioeconomic components. Then, using Conesa's methodology (1997), the importance matrix was applied and it was possible to identify that the main negative impact is air pollution, by the generation of bad smells with a value of -60 in the matrix, mainly due to the accumulation of large quantities of excreta. Another important impact, although of a negative nature, is the contamination of the soil with a value of -56, caused by the direct spillage of water contaminated with detergents and other chemicals that alter its properties. It was established that the activities of the farm in the operation and closure phase generate positive impacts, for example: jobs and dynamization of the economy. Based on the results obtained, an environmental management plan was drawn up that allowed the application of strategic activities such as, among others, the execution of live barriers that will help in the elimination of bad smells; and thus, to be able to mitigate and compensate the negative impacts and strengthen the positive impacts found.